Nkx2.2+ progenitors generate somatic motoneurons in the chick spinal cord. - Hitoshi Gotoh (Public Library of Science (PLoS), 2012)
Heterogeneous classes of neurons are present in the spinal cord and are essential for its function. Expression patterns of transcription factors in neural progenitor cells determine neuron subtypes during development. Nkx2.2 is expressed in the progenitor cell pool located just ventrally to the Olig2-positive pool and is indispensable for V3 interneuron generation in the spinal cord and also for visceral motoneuron generation in the hindbrain. However, whether Nkx2.2-positive progenitor cells generate diverse classes of neuron is not fully understood. Using a chick lineage tracing method in a genetically-defined manner, we found that Nkx2.2-expressing progenitor cells differentiate into general visceral motoneurons as well as sim1-positive V3 interneurons. Surprisingly, we further observed that Nkx2.2-expressing progenitors differentiate into somatic motoneuron. Our findings suggest that the different classes of motoneurons are derived from more complex sources than were previously expected in the chick spinal cord.